Experiences of Peer Interaction Amongst Autistic LGBTQ+ Youth in Secondary Schools - Comeau, Brianna (Canadian Social Work Review / Revue canadienne de service social, 2025)
This article highlights the importance of supporting the LGBTQ+ autistic community in the secondary school environment. While there is general agreement that schools need to be safe spaces, there is a dearth of literature understanding how schools can be safe spaces for individuals identifying as autistic and LGBTQ+. Using qualitative data from videoconference (Zoom) interviews with six LGBTQ+ autistic youth in Ontario secondary institutions, this study examined how interactions with peers shape identity, mental health, well-being, and social belonging. Informed by intersectionality theory and by critical perspectives on neurodiversity, this study found that LGBTQ+ autistic youth faced discrimination through microaggressions, peer victimization, and stereotyping, which led to feelings of low levels of safety in their school environments. Participants also had positive, affirming experiences relating to peers who would advocate and recognize LGBTQ+ and autistic identities. Participants spoke about supporting other peers who experienced similar challenges. This research has implications for social work practice, as it points to the importance of developing mentorship opportunities, implementing anti-discriminatory training and policies, respecting self-identification, and engaging in self-reflection to foster increased well-being and safety for LGBTQ+ autistic youth in school settings.